Effect of Liner Characteristics on the Acoustic Performance of Duct Systems - OTHMANI, Chokri; HENTATI, Taissir; TAKTAK, Mohamed; ELNADY, Tamer; FAKHFAKH, Tahar; HADDAR, Mohamed (Archives of Acoustics, 2015)
Porous materials are used in many vibro-acoustic applications. Different models describe their performance according to material’s intrinsic characteristics. In this paper, an evaluation of the effect of the porous and geometrical parameters of a liner on the acoustic power attenuation of an axisymmetric lined duct was performed using multimodal scattering matrix. The studied liner is composed by a porous material covered by a perforated plate. Empirical and phenomenal models are used to calculate the acoustic impedance of the studied liner. The later is used as an input to evaluate the duct attenuation. By varying the values of each parameter, its influence is observed, discussed and deduced.